2021
DOI: 10.3920/jiff2020.0002
|View full text |Cite
|
Sign up to set email alerts
|

Does sous-vide cooking preserve the chemical and volatile composition of Atlantic salmon (Salmo salar L.) fedHermetia illucens larvae meal?

Abstract: Physico-chemical characteristics and volatile organic compounds (VOCs) of fillets from Atlantic salmon fed diets with two substitution levels of fishmeal by defatted Hermetia illucens larvae meal (0 and 100%; H0, H100) were examined as raw and subjected to boiling and sous-vide (SV) cooking methods. H100 diet increased fillet saturated fatty acid content, thus negatively affecting the lipid health indexes. H100 was also associated with high levels of the n-3 fatty acids eicosapentaenoic and docosahexaenoic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 24 publications
4
6
0
Order By: Relevance
“…Our results support the view that the protein and lipid content are related to the dry matter content of fish samples. This is consistent with findings from other studies of protein content [5,8,37], as well as toward the lipid content [4]. All this indicate an inverse relationship between moisture content and other macronutrients.…”
Section: Proximate Composition and Fatty Acids Profile In Salmonsupporting
confidence: 92%
See 4 more Smart Citations
“…Our results support the view that the protein and lipid content are related to the dry matter content of fish samples. This is consistent with findings from other studies of protein content [5,8,37], as well as toward the lipid content [4]. All this indicate an inverse relationship between moisture content and other macronutrients.…”
Section: Proximate Composition and Fatty Acids Profile In Salmonsupporting
confidence: 92%
“…These findings were in accordance with the results of model research on salmon [30,31] and sous-vide processed seafood [32]. Husein et al [8] have reported that a sous-vide salmon fillet had higher moisture than a boiled one. Other authors confirmed a higher cooking loss of salmon baked in foil than steamed [6,7].…”
Section: Technological Characteristics Of Processed Salmonsupporting
confidence: 89%
See 3 more Smart Citations